2012
DOI: 10.1089/scd.2011.0073
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Embryonic Stem Cell–Derived Retinal Progenitors into Retinal Cells by Sonic Hedgehog and/or Retinal Pigmented Epithelium and Transplantation into the Subretinal Space of Sodium Iodate–Injected Rabbits

Abstract: Transplantation of retinal cells has recently provided a promising therapeutic approach for retinal degeneration. Here, we differentiated initially retinal progenitors (RPs) from adherent feeder-free human embryonic stem cells (hESCs) with the use of defined media supplemented with a specific combination of growth factors. The differentiated RPs highly (>80%) expressed related molecular features that included Six3 at an early stage in addition to Crx, Rx, Pax6, Otx2, and Chx10 at later stage. Next, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 41 publications
1
30
0
1
Order By: Relevance
“…The authors reported that these ES-derived RPE-like cells expressed typical RPE markers, such as ZO-1, RPE65, CRALBP, and Mertk, had extensive apical microvilli, and were able to phagocytize latex beads. The cells enhanced photoreceptor survival upon transplantation into the subretinal space of Royal College of Surgeons (RCS) rats, a well-established model of AMD (Amirpour et al, 2012). Haruta et al (2004) had originally reported successful transplantation of ES-derived RPE cells into the RCS rat subretinal space with enhanced survival of host photoreceptor cells (Haruta et al, 2004).…”
Section: Hesc-rpementioning
confidence: 99%
“…The authors reported that these ES-derived RPE-like cells expressed typical RPE markers, such as ZO-1, RPE65, CRALBP, and Mertk, had extensive apical microvilli, and were able to phagocytize latex beads. The cells enhanced photoreceptor survival upon transplantation into the subretinal space of Royal College of Surgeons (RCS) rats, a well-established model of AMD (Amirpour et al, 2012). Haruta et al (2004) had originally reported successful transplantation of ES-derived RPE cells into the RCS rat subretinal space with enhanced survival of host photoreceptor cells (Haruta et al, 2004).…”
Section: Hesc-rpementioning
confidence: 99%
“…39,11 The work presented here has further advanced our understanding of this model. Using both in vitro and mouse models, interactions between the oxidative effects of NaIO 3 on RPE and photooxidative stress imposed by lipofuscin bisretinoid also have been revealed.…”
Section: Discussionmentioning
confidence: 67%
“…16 In recent years, NaIO 3 administration in rats and mice has been used to model the atrophic lesions that are a feature of AMD 7 and has been favored as a means to denude RPE in advance of cell therapy. 4,5,810 …”
mentioning
confidence: 99%
“…In rats, photoreceptor degeneration can be prevented by subretinal transplantation of human fetal lung fibroblasts expressing the ciliary neurotrophic factor gene [66] , and laser-induced choroidal neovascularization can be inhibited by subretinal transplantation of RPE overexpressing fibulin-5 [67] . Of all of the cell types, progenitor cells and stem cells, such as human neural progenitor cells [68] , human retinal progenitor cells [69] , progenitor cells from the porcine neural retina [70] , forebrain progenitor cells [71] , brain-derived precursor cells [72] , human embryonic stem cell-derived retinal progenitors [73] , human RPE stem cells [74] , human bone marrow mesenchymal stem cells [75] , and rat mesenchymal stem cells [76] , are the most popular when given subretinally for cell replacement therapy for retinal degeneration. All these cells are considered to have the capability to survive and migrate into retinal layers and restore retina function or induce cell regeneration in different types of retinal cells when delivered via the subretinal route.…”
Section: Gene Therapymentioning
confidence: 99%